Old Belarusian encyclicals of the 16 th–17 th centuries: evolution of church religious epistolary communications - Zuyeva, Olga V. (Journal of the Belarusian State University. Philology, 2026)
The article examines the formula and linguistic features of ten Old Belarusian encyclicals from the spaces of Slavia Orthodoxa and Slavia Uniata of the 16 th–17 th centuries. Obligatory and optional elements of the formula are identified, means of their verbalisation are described, taking into account diachronic changes, phenomena of discourse interaction within the text are demonstrated. Features inherited from Old Russian letters and unchanged throughout the selected period, as well as new features reflecting language contacts, are identified. It is revealed that the majority of letters were written in Old Belarusian with varying degrees of polonisation and with the infiltration of Church Slavonic elements. Three texts by representatives of Slavia Orthodoxa from the late 16 th century were written in a hybrid Church Slavonic – Old Belarusian language with a significant predominance of Church Slavonic means at different levels. Thus, epistolary writing serves as a sphere for preserving communications in Church Slavonic in the Grand Duchy of Lithuania.